Corruption, shadow economy and deforestation: Friends or strangers? - Adeline-Cristina Cozma; Corina-Narcisa Cotoc; Viorela Ligia Vaidean; Monica Violeta Achim (Risks, 2021)
This study aims to reveal the connection between corruption and shadow economy, on one hand, and deforestation, on the other. The research considers 131 countries from all over the world, in the timeframe between the years 2012 and 2020, and it reveals that corruption and shadow economy positively influence deforestation. Determinants like democratic governance quality, press freedom, wood export share, and culture are also key factors in implementing the right, efficient countermeasures aimed at reducing the levels of illegal deforestation and sustainably managing the forestland. The importance of this study is to provide a solid quantitative basis to decision-makers that come across this problem of illegal logging through a better, fact-based understanding of the phenomenon.
Keywords: 330; corruption; deforestation; illegal logging; shadow economy; sustainability; timber mafia; wooden mafia